A quantum crystallographic approach to short hydrogen bonds. Issue 35 (13th August 2021) - Saunders, Lucy K.; Pallipurath, Anuradha R.; Gutmann, Matthias J.; Nowell, Harriott; Zhang, Ningjin; Allan, David R.
Abstract : Mapped electron density and ab initio modelling reveal how H-atom position and molecular environment tune short hydrogen bond characteristics and properties. Abstract : In this work we use high-resolution synchrotron X-ray diffraction for electron density mapping, in conjunction with ab initio modelling, to study short O—H⋯O and O + —H⋯O − hydrogen bonds whose behaviour is known to be tuneable by temperature. The short hydrogen bonds have donor–acceptor distances in the region of 2.45 Å and are formed in substituted urea and organic acid molecular complexes of N, N ′-dimethylurea oxalic acid 2 : 1 (1 ), N, N -dimethylurea 2, 4-dinitrobenzoate 1 : 1 (2 ) and N, N -dimethylurea 3, 5-dinitrobenzoic acid 2 : 2 (3 ). From the combined analyses, these complexes are found to fall within the salt-cocrystal continuum and exhibit short hydrogen bonds that can be characterised as both strong and electrostatic (1, 3 ) or very strong with a significant covalent contribution (2 ). An additional charge assisted component is found to be important in distinguishing the relatively uncommon O—H⋯O pseudo-covalent interaction from a typical strong hydrogen bond. The electron density is found to be sensitive to the extent of static proton transfer, presenting it as a useful parameter in the study of the salt–cocrystal continuum. From complementary calculated hydrogen atom potentials, we attribute changes in proton position to the molecular environment. Calculated potentials also show zero barrier to proton migration, forming an 'energy slide' between the donor and acceptor atoms. The better fundamental understanding of the short hydrogen bond in the 'zone of fluctuation' presented in a salt-cocrystal continuum, enabled by studies like this, provide greater insight into their related properties and can have implications in the regulation of pharmaceutical materials.